Counseling of the Importance of Family Medicine Plants (TOGA) as an Effort to Improve Healthy Lifestyle at the SDN Centong, Gondang District, Mojokerto Regency - Puguh Satya Hasmara; Ilmul Ma’arif (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2022)
Educational institutions are seen as a strategic place to promote health. Schools are also effective institutions for realizing health education, where students can be taught about the meaning of healthy behavior and back to nature. In addition, school age is a golden age to instill back to nature values ​​and has the potential as an agent of change to promote back to nature both in the school, family, and community environment. School teachers as the target of promotion of back to nature, especially the basic education level (SD and SMP). This is because the teacher can transmit it to students, because this age group of students is easy to accept new innovations and has a strong desire to convey the knowledge and information they receive to others. School children are a group of children whose age is balanced. Some examples of the implementation of back to nature in schools can be conveyed, for example counseling on the importance of TOGA. SDN Centong, Gondang Subdistrict, Mojokerto Regency has a fairly large yard, which holds a lot of potential for the use of natural resources, one of which is the use of the yard to plant TOGA. TOGA is still something that is not yet known by students. Therefore, there is a need for counseling on the importance of planting TOGA in this school. This community service program aims to provide teachers with an understanding of the importance of TOGA so that it can be conveyed to students. The implementation method is (1) pretest, (2) counseling, (3) discussion and question and answer, (4) posttest. This activity involved the entire Board of Teachers and Employees of SDN Centong. The total value increased by 116 from 1000 to 1116, the average also increased by 9 from 71 to 80. Then the highest value increased by 8 from 84 to 92, and the lowest value also increased by 12 from 60 to 72 There was an increase in all scores from the pretest and posttest, this indicates that this outreach activity was running effectively because it could significantly increase the understanding of the teachers and employees of SDN Centong.